HYGIENIC EVALUATION OF THE BACTERIAL CONTAMINATION OF A MULTIDISCIPLINARY HOSPITAL IN DONBASS IN MODERN CONDITIONS. PART II. DYNAMICS DURING THE WAR YEARS - Вячеслав Александрович Бондаревский-Колотий; Дмитрий Олегович Ластков; Анна Григорьевна Сихарулидзе (Медицина в Кузбассе)
A comparative hygienic assessment of bacterial contamination of air, washes, sterility of materials, skin of the operating field and surgeons' hands in the units of a multidisciplinary hospital in different time periods of the war period. Rates of sterility and swabbing contamination define periods of the onset of military conflict, and rates of air contamination define periods of COVID-19 pandemic and special military operation.